2018
DOI: 10.1002/advs.201800004
|View full text |Cite
|
Sign up to set email alerts
|

Mucoadhesive Cationic Polypeptide Nanogel with Enhanced Penetration for Efficient Intravesical Chemotherapy of Bladder Cancer

Abstract: Initially, chemotherapy is effective for treatment of bladder cancer after transurethral resection of the bladder. However, certain patients progressively become unresponsive after multiple treatment cycles, which results from the rapid and almost complete excretion of clinically used formulations of antineoplastic agents with urinary voiding. Improving the mucoadhesiveness and penetrability of chemotherapeutic drugs are key factors in treatment of advanced bladder cancer. Here, a smart disulfide‐crosslinked p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 105 publications
(67 citation statements)
references
References 30 publications
0
66
0
1
Order By: Relevance
“…Previous clinical practice has shown that the clinical e ect of montelukast alone as a leukotriene regulator in the treatment of bronchial asthma needs to be further improved. Polysaccharide served as anti-tumor drug has been well studied in various types of tumor cells [7,8]. In the present study, we established a murine asthmatic model and demonstrated that asthma model mice, challenged with APS and budesonide, exhibited improved airway hyper-responsiveness.…”
Section: Discussionmentioning
confidence: 54%
“…Previous clinical practice has shown that the clinical e ect of montelukast alone as a leukotriene regulator in the treatment of bronchial asthma needs to be further improved. Polysaccharide served as anti-tumor drug has been well studied in various types of tumor cells [7,8]. In the present study, we established a murine asthmatic model and demonstrated that asthma model mice, challenged with APS and budesonide, exhibited improved airway hyper-responsiveness.…”
Section: Discussionmentioning
confidence: 54%
“…Furthermore, many chemotherapeutic drugs are hydrophobic, which can lead to poor absorption and bioavailability. New chemotherapeutics and existing chemotherapeutics with new formulations have recently been developed to address these limitations (Qi et al, 2017;Guo et al, 2018). Application of nanomaterials as chemotherapeutic DDSs has also been studied frequently.…”
Section: Chemotherapymentioning
confidence: 99%
“…Review in vivo for neat nanogels, 23,192,193 and they should be done also for the functionalized ones and then validated in humans. Indeed, current delivery systems could find problems like quick clearance by the immune system and low selectivity and cell targeting, together with difficulty in crossing biological barriers.…”
Section: Acs Applied Nano Materialsmentioning
confidence: 99%